2010
DOI: 10.1021/es903436v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Sintering-Resistant Sorbents for CO2 Capture

Abstract: Sorbents for high temperature CO2 capture are under intensive development owing to their potential applications in advanced zero emission power, sorption-enhanced steam methane reforming for hydrogen production and energy storage systems in chemical heat pumps. One of the challenges in the development is the prevention of sintering of the sorbent (normally a calcium oxide derivative) which causes the CO2 capture capacity of the material to deteriorate rapidly after a few cycles of utilization. Here we show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
184
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(189 citation statements)
references
References 22 publications
5
184
0
Order By: Relevance
“…calcium acetate, calcium ethanoate (Lu et al, 2006;Lu, H. et al, 2008;Liu et al, 2010a) with particular success using a MgO support (Liu et al, 2010b) to similarly enhance the reactive surface area; dispersal of CaO within an inert porous matrix such as mayenite (Li et al, 2005;Li et al, 2006;Pacciani et al, 2008a) to improve mechanical stability; and use of cementitious binders (Manovic and Anthony, 2009a; to improve mechanical stability. Sorbent reactivity can be periodically improved by hydration of calcined sorbent, though this is often at the expense of mechanical strength of the sorbent (Hughes et al, 2004;Fennell et al 2007b;Manovic and Anthony, 2007;Manovic and Anthony., 2008a;Sun et al, 2008;Zeman, 2008).…”
Section: Sorbent Performancementioning
confidence: 99%
“…calcium acetate, calcium ethanoate (Lu et al, 2006;Lu, H. et al, 2008;Liu et al, 2010a) with particular success using a MgO support (Liu et al, 2010b) to similarly enhance the reactive surface area; dispersal of CaO within an inert porous matrix such as mayenite (Li et al, 2005;Li et al, 2006;Pacciani et al, 2008a) to improve mechanical stability; and use of cementitious binders (Manovic and Anthony, 2009a; to improve mechanical stability. Sorbent reactivity can be periodically improved by hydration of calcined sorbent, though this is often at the expense of mechanical strength of the sorbent (Hughes et al, 2004;Fennell et al 2007b;Manovic and Anthony, 2007;Manovic and Anthony., 2008a;Sun et al, 2008;Zeman, 2008).…”
Section: Sorbent Performancementioning
confidence: 99%
“…These approaches include: the use of dopants [10] [11] [12]; hydration and steam reactivation [13] [14] [15]; thermal pre-sintering [16] [17]; spacer molecule incorporation [18] and sintering resistant internal supports [19] [20]. Recently, Zhao et al [21] has reported a CaO-based sorbent incorporating a supporting structure composed of dicalcium silicate (Ca2SiO4, from here on referred to as C2S which is common notation of this compound in the cement industry) which enabled the sorbent to retain a very high proportion of its carrying capacity throughout many cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Adsorption of N 2 on a sorbent was performed on a TriStar 3000 instrument (Micromeritics Instrument Corporation, Norcross, GA, USA) in order to evaluate its Brunauer, Emmett and Teller (BET) surface area and pore volume, parameters of which were used to calculate the initial surface area and porosity of CaO and CaCO 3 . Before the test, the fresh sorbent was degassed at 250 °C overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, its performance in the cycling process rapidly decreases due to sintering, attrition and ash fouling [2]. To overcome the loss in CO 2 sorption capacity over cycles, synthetic CaO based sorbents have been developed [3,4] and tested in a laboratory scale process [4]. Note that relatively low CaO content in these samples allows for substantial improve the performance of the synthetic sorbents over many cycles.…”
Section: Introductionmentioning
confidence: 99%